The Effect of the Index Card Match Learning Model on the Motivation and Science Learning Outcomes of Seventh Grade Students at SMP N 1 Jujuhan, Bungo Regency - Yulia Fridayani; Widia Kemala Sari (SEMESTA: Journal of Science Education and Teaching, 2026)
This study aims to determine the effect of the Index Card Match learning model on the motivation and science learning outcomes of seventh-grade students at SMP N 1 Jujuhan, Bungo Regency. This study is quantitative in nature with a quasi-experimental approach using a nonequivalent control group design. The sample was selected through purposive sampling consisting of two classes, namely experimental class VII C and control class VII B with a total of 46 students. Data were collected through motivation questionnaires and learning achievement tests (pretest and posttest).  This study conducted statistical analysis using SPSS with normality, homogeneity, and parametric tests, namely the t-test to determine the effect of the Index Card Match learning model. The results showed that the average learning motivation score of the experimental class was 81.43 (high category) and the learning outcome (posttest) was 74.26. The hypothesis test results for learning motivation showed that Sig.< α = 0,03 < 0,05, indicating a significant difference between the learning motivation of students taught using the Index Card Match model compared to the conventional model. The results of the hypothesis test for learning outcomes showed that Sig.< α = 0,031 < 0,05, so it can be concluded that the Index Card Match model has a significant effect on increasing motivation and learning outcomes in science. The implications of this study show that the Index Card Match learning model is effective in creating an interactive and collaborative learning environment, so it can be used as an alternative for educators to improve the quality of science learning in schools.